No sex‐specific markers detected in bluegill sunfish Lepomis macrochirus by AFLP - Z. X. Gao; H. P. Wang; H. Yao; L. Tiu; W. M. Wang (Journal of Fish Biology, 2010)
The amplified fragment‐length polymorphism (AFLP) technique was used to identify sex‐specific markers in bluegill sunfish. A total of 12 835 loci were produced by 256 primer combinations, of which nine (0·73‰) exhibited presumed sex‐associated amplifications in the pooled samples; however, none of which revealed sex specificity upon individual evaluation.